2001
DOI: 10.1152/jn.2001.85.3.1299
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Anesthesia and Cerebral Blood Flow Changes Elicited by Vibrotactile Stimulation: A Positron Emission Tomography Study

Abstract: We investigated the effects of the general anesthetic agent propofol on cerebral structures involved in the processing of vibrotactile information. Using positron emission tomography (PET) and the H(2)(15)O bolus technique, we measured regional distribution of cerebral blood flow (CBF) in eight healthy human volunteers. They were scanned under five different levels of propofol anesthesia. Using a computer-controlled infusion, the following plasma levels of propofol were targeted: Level W (Waking, 0 microg/ml),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
60
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(66 citation statements)
references
References 21 publications
5
60
0
1
Order By: Relevance
“…Human positron emission tomography (PET) studies measuring changes in CBF at different levels of propofol anesthesia did not show increasing increments to sensory stimulation at deeper levels of anesthesia (35), as would be expected from our results. However, the authors acknowledged that localized changes in CBF were confounded by elevated blood pCO 2 (that increased with depth of anesthesia), which in turn raised CBF globally.…”
Section: Discussionsupporting
confidence: 85%
“…Human positron emission tomography (PET) studies measuring changes in CBF at different levels of propofol anesthesia did not show increasing increments to sensory stimulation at deeper levels of anesthesia (35), as would be expected from our results. However, the authors acknowledged that localized changes in CBF were confounded by elevated blood pCO 2 (that increased with depth of anesthesia), which in turn raised CBF globally.…”
Section: Discussionsupporting
confidence: 85%
“…Our experiment cannot distinguish between direct propofol modulation of the striatum itself and striatal deafferentation secondary to drug activity at another site such as the cortex, brainstem or indeed the thalamus (Abulafia et al, 2009). This is a parallel problem to that raised by Bonhomme and colleagues, who found cortical activation to be reduced at lower doses than those required to reduce activation within the thalamus (Bonhomme et al, 2001).…”
Section: Discussionmentioning
confidence: 86%
“…Fiset et al (1999) found that propofol preferentially decreased regional cerebral blood flow (rCBF) in the thalamus, midbrain, cuneus, precuneus, posterior cingulate, and orbitofrontal cortex. Bonhomme et al (2001) found that propofol reduced rCBF changes during vibrotactile stimulation at doses below those required to suppress the thalamic rCBF response. We aimed to extend these important findings, harnessing the superior temporal resolution of functional magnetic resonance imaging (fMRI) to test the hypothesis that decreases in functional connectivity occur with deepening sedation.…”
Section: Introductionmentioning
confidence: 91%
“…Regional cerebral blood flow (rCBF) PET studies have shown that propofol-induced unresponsiveness is associated most with decreased blood flow in the thalamus and PCC/precuneus (Bonhomme et al, 2001;Fiset et al, 1999;Kaisti et al, 2003;Schlunzen et al, 2012;Xie et al, 2011). Most severe reductions in glucose use were seen in the thalamus, parietal and frontal DMN regions, and occipital lobe (Schlunzen et al, 2012;Sun et al, 2008).…”
Section: Total Brain Connectivitymentioning
confidence: 99%